The Prominent Spring Bloom and Its Relation to Sea‐Ice Melt in the Sea of Okhotsk, Revealed by Profiling Floats - S. Kishi; K. I. Ohshima; J. Nishioka; N. Isshiki; S. Nihashi; S. C. Riser (Geophysical Research Letters)
Abstract Seven profiling floats equipped with oxygen sensors deployed in the Sea of Okhotsk provide time series data for 33 cases of spring phytoplankton bloom period, including 9 cases in which sea ice existed just before the bloom (prior‐ice case). As an index of biological productivity, we calculated net community production (NCP) based on the increasing oxygen rate using the Redfield ratio. The total NCP in the euphotic layer averaged for prior‐ice cases is 31.3 mmolC m−2 day−1), ∼3 times higher than that of non‐ice cases. In addition to intensification of surface stratification, other factors of sea‐ice melt likely enhance the bloom. The influence of sea‐ice melt is particularly large in the southwestern region, where the iron availability likely limits phytoplankton growth. A suggested scenario is that when the sea ice containing sediment/iron is transported from the northern shelves, a prominent bloom is induced via the iron supply by sea‐ice melt.